Efficacy of smear layer removal at apical third of root canal by different irrigation regimens using XP-endo Shaper: an in vitro SEM study - Varma, K Madhu; Mavidi, Jagapathi Babu; Satish, R Kalyan; Indukuri, Sai Lakshmi; Manishaa, Bondada; Gadde, Praveen (International Journal of Dental Materials, 2024)
Background: Effective root canal therapy relies heavily on irrigation, as it is the sole method capable of reaching the internal anatomy of the root canal that remains inaccessible with mechanical instrumentation.Aim: To compare the efficacy of different irrigation regimes on smear layer removal with XP-endo Shaper at the apical third of the root canal in lower premolars under a scanning electron microscope.Materials and methods: Forty-four human single-rooted lower premolars were collected and decoronated to a standard length. Teeth were categorized into four groups based on the irrigation regimes: distilled water (DW Group), 5.25% NaOCl and 17% EDTA (SE Group), super-oxidised water and 17% EDTA (SPO Group), TWIN KLEEN solution (TK Group). Scanning electron microscopic evaluation was done at 3 mm from the apex to analyse the remaining amount of smear layer. Kruskal-Wallis test and Mann–Whitney U test were employed in this study.Results: On comparing the ability of four different irrigation regimes to remove the smear layer, the SPO and SE Groups showed significantly higher smear layer removal (p